2013
DOI: 10.1128/aem.00404-13
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional Response of Nitrifying Communities to Wetting of Dry Soil

Abstract: The first rainfall following a severe dry period provides an abrupt water potential change that is both an acute physiological stress and a defined stimulus for the reawakening of soil microbial communities. We followed the responses of indigenous communities of ammonia-oxidizing bacteria, ammonia-oxidizing archaea, and nitrite-oxidizing bacteria to the addition of water to laboratory incubations of soils taken from two California annual grasslands following a typically dry Mediterranean summer. By quantifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
85
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(97 citation statements)
references
References 60 publications
(51 reference statements)
11
85
1
Order By: Relevance
“…Meanwhile, this result suggests that AOA is more adaptable to drought or a low-nitrogen environment than AOB. Some studies have confirmed this conclusion (Placella and Firestone 2013;Verhamme et al 2011), and the extensive adaptability of AOA may explain why AOA had much greater numbers than AOB and occupied the main ecological niche of ammonia oxidizing process in the desert area. AOA and AOB abundance had a close relationship with PAO (r = 0.642, P \ 0.01 and r = 0.551 P \ 0.05 [ Table 2]) indicating that both AOA and AOB play dominant roles in ammoxidation in the whole region.…”
Section: Correlation Between Pao Aoa and Aob Abundance And Environmementioning
confidence: 56%
See 1 more Smart Citation
“…Meanwhile, this result suggests that AOA is more adaptable to drought or a low-nitrogen environment than AOB. Some studies have confirmed this conclusion (Placella and Firestone 2013;Verhamme et al 2011), and the extensive adaptability of AOA may explain why AOA had much greater numbers than AOB and occupied the main ecological niche of ammonia oxidizing process in the desert area. AOA and AOB abundance had a close relationship with PAO (r = 0.642, P \ 0.01 and r = 0.551 P \ 0.05 [ Table 2]) indicating that both AOA and AOB play dominant roles in ammoxidation in the whole region.…”
Section: Correlation Between Pao Aoa and Aob Abundance And Environmementioning
confidence: 56%
“…Furthermore, many researchers found that soil physical and chemical properties, such as pH, temperature, moisture, substrate concentration, soil types, and land-use types, played important roles in niche separation between AOA and AOB (Gubry-Rangin et al 2011;O'Sullivan et al 2013;Placella and Firestone 2013;Verhamme et al 2011;Yao et al 2013). In addition to the influence of soil properties, heavy metal, which has turned out to be a key factor in regulating microbial nitrogen cycle (Morel and Price 2003), could exert effects on ammonia oxidizers.…”
mentioning
confidence: 99%
“…Our results add to a large body of work suggesting that induction of many acyl-HSL QS systems is both cell density and growth phase dependent (13). Although NOB are generally found at low cell densities in soils (10 5 to 5 Ï« 10 5 nxrA copies g ÏȘ1 ) (56,57), heterogeneous spatial distribution and restricted diffusion under unsaturated soil conditions could, in fact, permit autoinducers to reach effective localized concentrations (11). Indeed, our experiments confirmed that the QS system of N. winogradskyi was induced at a cell density of approximately 3.2 Ï«10 6 cells ml ÏȘ1 during batch culture (Fig.…”
Section: Discussionmentioning
confidence: 74%
“…It is difficult to draw conclusions about the role of moisture in AOA /AOB niche differentiation due to dissimilarities in experimental design. Nevertheless, it is well possible that AOB and AOA develop different strategies to react to changes in soil moisture, e.g., via the regulation of amoA gene transcription (Placella and Firestone, 2013).…”
Section: Discussionmentioning
confidence: 99%